2018
DOI: 10.1177/1069072718793966
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Interest Congruence and College Major Satisfaction: Evidence From the Basic Interest Measures

Abstract: The relation between the degree of interest congruence (i.e., person–environment fit in interest domain) and career satisfaction has been inconsistent and generally low across studies. Interest congruence is typically measured at the broadband general interest level, bound within Holland’s Realistic, Investigative, Artistic, Social, Enterprising, and Conventional (RIASEC) framework, and largely based on the match of the high-point interest codes between persons and environments. Using two cross-cultural colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In this study, a low degree positive relationship was found between person-major fit and major satisfaction, in other words, person-major fit significantly predicts major satisfaction. In the literature, several studies support (Bai & Liao, 2018;Fu et al, 2019;Mathis et al, 2017;Nafziger et al, 1975) and others do not support (Milsom & Coughlin, 2017;Pozzebon et al, 2014) this finding. However, previous studies have shown that the correlation between the two variables is low or moderate, which is similar to the results of this study (Bai & Liao, 2018;Hoeglund & Hansen, 1999;Tsabari et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this study, a low degree positive relationship was found between person-major fit and major satisfaction, in other words, person-major fit significantly predicts major satisfaction. In the literature, several studies support (Bai & Liao, 2018;Fu et al, 2019;Mathis et al, 2017;Nafziger et al, 1975) and others do not support (Milsom & Coughlin, 2017;Pozzebon et al, 2014) this finding. However, previous studies have shown that the correlation between the two variables is low or moderate, which is similar to the results of this study (Bai & Liao, 2018;Hoeglund & Hansen, 1999;Tsabari et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…This fit mitigates the effects of psychological barriers that negatively affect individuals while completing their career development tasks (Jiang, 2017). While some studies have shown that person-major fit significantly predicts major satisfaction (Bai & Liao, 2018;Fu et al, 2019;Mathis et al, 2017;Nafziger et al, 1975), other studies have shown contrary results (Milsom & Coughlin, 2017;Pozzebon et al, 2014). In summary, although previous studies focused on teachers' job satisfaction, examining education students' major satisfaction was neglected.…”
Section: Person-major Fit and Major Satisfactionmentioning
confidence: 97%
“…To measure the six RIASEC orientations, we used the research instrument developed by Liao, Armstrong, and Rounds (2008). This instrument was explicitly designed to for usage in the public domain, as an alternative to commercial instruments which can limit the range of questions investigated in empirical research (Goldberg, 1999), and it has attracted considerable research use (Bai & Liao, 2018; Fouad, Singh, Cappaert, Chang, & Wan, 2016). The scale consists of 48 items that describe different work tasks, with items rated on a scale from 1 ( greatly dislike ) to 5 ( greatly enjoy ).…”
Section: Methodsmentioning
confidence: 99%
“…However, they are measured as explicit, declarative interests, while in our research, we consider implicit preferences or interests. Most questionnaires derived from Holland’s theory [ 20 , 21 , 22 ] assess such interests by means of explicit, verbal questions, thus introducing possible biases associated with conformity, acquiescence, or desirability. In our approach, interests are assessed through behaviour to avoid such biases.…”
Section: Introductionmentioning
confidence: 99%